Nonlinear bending analysis of trapezoidal panels under thermo-mechanical load - Emarti Kumari; Shiv Lal (Forces in Mechanics, 2022)
The nonlinear bending responses of trapezoidal panels under thermal load are investigated here using the higher order degenerated shell element. First-order shear deformation theory is used here and employed the finite element method with account of von Karman's geometric nonlinearity. The nonlinear governing equations are solved by using Newton Raphson method. First, checked the efficacy of higher order degenerated shell element with available published results of symmetric trapezoidal plates under mechanical load and curved panel under thermal load. In this article authors investigated the effect of boundary conditions, radius to span (R/a) ratio, cord to span (c/a) ratio, aspect (a/b) ratio, and lamination sequence on the nonlinear static response of trapezoidal panels under thermal environment. Moreover, new results for nonlinear bending behavior of symmetric trapezoidal cylindrical panels under uniform temperature are presented here that will be useful for future research and work as bench mark results.